PERSEPSI MAHASISWA TENTANG MATA KULIAH STATISTIK SERTA PENGARUHNYA TERHADAP PRESTASI BELAJAR STATISTIK MAHASISWA IKIP PGRI MADIUN - Afifah, Sofia Nur; Wicaksana, Ervan Johan (Jurnal Penelitian LPPM (Lembaga Penelitian dan Pengabdian kepada Masyarakat) IKIP PGRI MADIUN, 2016)
Students perceptions of Statistics related to the their learning outcomes. Perception is the process of consciousness, namely the consciousness of an object which delivers to the understanding, the process or the ability to feel the results of knowledge and so obtained with a feeling and sense or intuition that is abstract. Perception will lead someone on giving meaning to the notion of something. Students perceptions of subjects Statistics describes the level of students knowledge and understanding of the statistics. The purposes of this study are: (1) determine the students perception of on Statistics, (2) determine the influence of students perception on Statistics. This study used the design of Mixed Methods, which consists of two types of research, thefirst one was qualitative research and another one was quantitative. The sample is taken from the students of fourth semester study program Primary Age Students Teachers Training IKIP PGRI Madiun in the Academic Year of 2013/2014 consists of 28 students. Data collection techniques used are questionnaires and documentation. Data analysis techniques in this study used a qualitative descriptive technique. In addition to these techniques are also used in the form of ahypothesis test Spearman test. Based on the results the following results: (1) Students Perceptions of Statistics Course outlines included into good category; (2) There is no influence of students perceptions in statistics course. It is evident in the results or the value of P = 0.124 (P > 0.05) and the value of r xy = 0.294, which means the relationship between students perceptions about Statistical study and the learningachievement is weak.Students perceptions of Statistics related to the their learning outcomes. Perception is theprocess of consciousness, namely the consciousness of an object which delivers to theunderstanding, the process or the ability to feel the results of knowledge and so obtained with afeeling and sense or intuition that is abstract. Perception will lead someone on giving meaning tothe notion of something. Students perceptions of subjects Statistics describes the level of studentsknowledge and understanding of the statistics. The purposes of this study are: (1) determine thestudents perception of on Statistics, (2) determine the influence of students perception onStatistics. This study used the design of Mixed Methods, which consists of two types of research, thefirst one was qualitative research and another one was quantitative. The sample is taken from thestudents of fourth semester study program Primary Age Students Teachers Training IKIP PGRIMadiun in the Academic Year of 2013/2014 consists of 28 students. Data collection techniquesused are questionnaires and documentation. Data analysis techniques in this study used aqualitative descriptive technique. In addition to these techniques are also used in the form of ahypothesis test Spearman test.Based on the results the following results: (1) Students Perceptions of Statistics Course outlinesincluded into good category; (2) There is no influence of students perceptions in statistics course.It is evident in the results or the value of P = 0.124 (P > 0.05) and the value of r xy = 0.294, whichmeans the relationship between students perceptions about Statistical study and the learningachievement is weak.